Primary coronary angioplasty in a nonagenarian - Baracioli,Luciano M. (2002)
A woman aged 98 years entered the tertiary hospital service with a picture of acute myocardial infarction of the extensive anterior wall, which began 4 hours earlier. Due to the large myocardial risk area suggested by the electrocardiogram, the patient was taken to the hemodynamics laboratory for the performance of emergency coronary arteriography, which revealed occlusion in the proximal third of the anterior descending artery. Primary angioplasty followed by stent grafting was successfully performed. The patient had a satisfactory evolution (Killip I) and was discharged from the hospital on the seventh postinfarction day. We discuss here aspects of thrombolysis and coronary percutaneous interventions in the aged.